Which expression is equivalent to (2r² + r - 1) - (3r² + 4r - 5) ?

A.) -r² - 3r + 4

B.) -r² + 5r - 6

C.) 5r² - 3r + 4

D.) 5r² + 5r - 6

A.) -r² - 3r + 4

B.) -r² + 5r - 6

C.) 5r² - 3r + 4

D.) 5r² + 5r - 6

(2r² + r - 1) - (3r² + 4r - 5)

= 2r² + r - 1 - 3r² - 4r + 5 {removed parentheses, distributing negative sign}

= -r² - 3r + 4 {combined like terms}

= 2r² + r - 1 - 3r² - 4r + 5 {removed parentheses, distributing negative sign}

= -r² - 3r + 4 {combined like terms}

**A.) -r² - 3r + 4**__Ask Algebra House__